Motivations for women’s participation in urban agriculture: a multivariate probit model analysis - Tayech Lemma; Mala Sharma (International Journal of Agricultural Sustainability)
Urban agriculture (UA) empowers women by providing economic opportunities, control over food, social connections, new skills, and improved health. Despite its importance, Ethiopian women's participation in UA remains low. This study aimed to examine the factors that influencing women's motivation to participate in UA in Hossana town, Ethiopia. We analysed survey data from 272 women participating in UA using a multivariate probit model. We identified four primary motivational dimensions: food security, economic reasons, social connection, and general well-being. The results revealed that combination of food security and economic motivations were the main drivers for women to participate in UA. The multivariate probit model results showed that age, education level, marital status, family size, employment status, non-urban farm income, farm experience, garden size, access to credit and markets, and the use of improved inputs all significantly influence the likelihood of women’s motivations to participate in UA. These findings provide valuable insights into the motivating factors driving women’s participation in UA and suggest the potential bundling of motivations. They lay the groundwork for more effective policies and programmes to support women's participation in this crucial sector of UA.